(untitled) (Colloquium Agrariae. ISSN: 1809-8215, 2022)
The objective of this work was to compare three methods of estimate the optimal plot size to evaluate the fresh matter productivity of forage sorghum (Sorghum bicolor (L.) Moench) sown in rows, evaluated in three cuts. Two uniformity trials (repetitions) were carried out. In each trial, three plant cuts were performed, totaling six uniformity trials (2 trials per cut × 3 cuts). The first cut was performed at 41 days after sowing (DAS), the second at 82 DAS and the third at 133 DAS. Fresh matter productivity was evaluated in 216 basic experimental units (BEU) of 1 m × 1 m (36 BEU per trial). The BEU was formed by two rows of 1.0 m in length, spaced 0.50 m between rows, totaling 1.0 m2. The optimal plot size was determined using the modified maximum curvature methods, the model linear response with plateau and the model quadratic response with plateau. The optimal plot size differs between the methods and decreases in the following order: model quadratic response with plateau (9.10 m2), model linear response with plateau (7.16 m2) and modified maximum curvature (4.13 m2). The optimal plot size to evaluate the fresh matter productivity of forage sorghum, sown in rows, evaluated in three cuts, is 7.16 m2 and the experimental precision stabilizes from this size on.